IMPACT OF NEW TECHNOLOGICAL DEVELOPMENTS ON EDUCATION AND LIFE SKILL DEVELOPMENT OF VISUALLY IMPAIRED AND DEAF-BLIND CHILDREN - Kumar, Anil; Singh, Gopal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This article examines the impact of new technological developments on education and life skill development of visually impaired and deaf-blind children. Advances in assistive technologies such as screen readers, braille displays, haptic devices, augmented or virtual reality, etc. have significantly improved access to information and educational activities for visually impaired and deaf-blind students. Technology has enhanced communication capabilities for these students through devices such as tactile communication boards, which enable interaction with peers and teachers. The use of technology helps visually impaired and deaf-blind children develop essential life skills such as communication, independent movement, time management, etc. Integrating accessible digital educational content software and platforms in classrooms promotes more inclusive and personalized learning experiences. Professional development for teachers on using assistive technology and creating accessible curriculum is crucial for creating effective learning environments. Challenges remain in areas such as availability and maintenance of teacher training equipment, assessing needs, and providing adequate information on assistive technology. Future innovations should focus on improving hardware, software, and developing new assistive technologies, especially for the disabled population. Primarily, the article surveys the literature to explore how technology serves as an empowering force for visually impaired and deaf-blind students, improving their learning, skill development, and inclusion in mainstream schooling.